2019
DOI: 10.1002/jee.20302
|View full text |Cite
|
Sign up to set email alerts
|

Comparing students' engineering and science aspirations from age 10 to 16: Investigating the role of gender, ethnicity, cultural capital, and attitudinal factors

Abstract: Background Women (along with minority ethnic and low-income communities) remain underrepresented in engineering, despite a thirty-year history of research and equality legislation. Compared to the US and other EU countries, this underrepresentation is particularly pronounced in the UK. While existing literature gives insights into factors shaping retention and progression in university engineering students, comparatively less is known about the development of school students' engineering aspirations.Purpose Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
(55 reference statements)
0
30
0
4
Order By: Relevance
“…While this article aimed specifically to investigate contributions of STEM‐related subject attitudes, we accept and acknowledge that other variables will be important to study and include in future modeling analyses to provide a more complete understanding of the multitude of factors relating to student's levels of science capital for this age group. Our ongoing work (Moote et al, , ) has begun to shed light onto this, documenting that gender, ethnicity, and cultural capital, and science self‐concept are important factors that explain a significant proportion of the variance not captured in the current set of analyses. Additionally, further research could explore how these background factors influence the relationship between subject‐specific attitudes and science capital.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…While this article aimed specifically to investigate contributions of STEM‐related subject attitudes, we accept and acknowledge that other variables will be important to study and include in future modeling analyses to provide a more complete understanding of the multitude of factors relating to student's levels of science capital for this age group. Our ongoing work (Moote et al, , ) has begun to shed light onto this, documenting that gender, ethnicity, and cultural capital, and science self‐concept are important factors that explain a significant proportion of the variance not captured in the current set of analyses. Additionally, further research could explore how these background factors influence the relationship between subject‐specific attitudes and science capital.…”
Section: Discussionmentioning
confidence: 94%
“…This article reports on students' responses to the following open‐ended survey question as an indicator of post‐18 aspirations, “What best describes the main area of your desired degree/course/subject of study?” Responses were coded into the relevant disciplines by two of the authors. Dichotomous variables were then created (e.g., Physics vs. non‐Physics) and a series of independent‐samples t ‐tests was conducted to compare levels of science capital among various STEM versus non‐STEM university study aspirations, building on the analyses reported in Moote et al (, ). The term “computer science” is used here as this data relates to university study aspirations, with “technology” being a broader discipline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Godwin and colleagues found that women have similar performance in engineering to boys, but lower confidence in their skills [8]. Moote et al [15] found genderlinked disparities in career aspirations in engineering, positing that this disparity shows how the traditional branding of engineering as masculine is still greatly affecting students' relationships to engineering. Some studies have found instances of gatekeeping in engineering, where young boys try to assert that engineering is not a female space, taking control of projects and not collaborating with female group members [3], [15].…”
Section: A Conceptual Frameworkmentioning
confidence: 99%
“…Moote et al [15] found genderlinked disparities in career aspirations in engineering, positing that this disparity shows how the traditional branding of engineering as masculine is still greatly affecting students' relationships to engineering. Some studies have found instances of gatekeeping in engineering, where young boys try to assert that engineering is not a female space, taking control of projects and not collaborating with female group members [3], [15]. Girls must navigate difficult-to-access, traditionally male spaces, and reconcile performance of engineering and feminine identities, which are considered socially incompatible, in order to construct an engineering identity [15].…”
Section: A Conceptual Frameworkmentioning
confidence: 99%